Learning the Amtsilati Method in Reading the Yellow Book of Ta’limul Muta’allim at the Raudhatul Muta'allimin Al-Baisuny Islamic Boarding School - Sari, Kartika; Dewi, Ratna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research aims to determine the Amtsilati method of reading the Yellow Book at the Raudlatul Muta'allimin Al-Baisuny Islamic Boarding School. To answer this question, this research uses qualitative research using descriptive methods. This research uses primary data sources and secondary data. Meanwhile, data collection techniques use observation, interviews and documentation. Then, the data analysis technique is through a data reduction process, data presentation stage and drawing conclusions and verification. The results of Amsilati's research in reading the Yellow Book show that the form of learning is using the Amtsilati method in the Amtsilati learning process it uses stages starting with the teacher reading the words in the yellow book then explaining the meanings and the students together reading nadzom-nadzom that has been given so that students become accustomed to it and memorise it more easily. Then, use media in learning, as well as practical learning time. Meanwhile, the supporting factor that influence the